A Modified General Regression Neural Network (MGRNN) with new, efficient training algorithms as a robust ‘black box’-tool for data analysis - Tomandl, Dirk; Schober, Andreas (Neural networks, 2001)
A Modified General Regression Neural Network (MGRNN) is presented as an easy-to-use ‘black box’-tool to feed in available data and obtain a reasonable regression surface. The MGRNN is based on the General Regression Neural Network by D. Specht [Specht, D. (1991). A General Regression Neural Network. IEEE Transactions on Neural Networks, 2(6), 568–576], therefore, the network's architecture and weights are determined. The kernel width of each training sample is trained by two supervised training algorithms. These fast and reliable algorithms require four user-definable parameters, but are robust against changes of the parameters. Its generalization ability was tested with different benchmarks: intertwined spirals, Mackey–Glass time series and P roben1. The MGRNN provides two additional features: (1) it is trainable with arbitrary data as long as a suitable metric exists. Particularly, it is unnecessary to force the data structure to vectors of equal length; (2) it is able to compute the gradient of the regression surface as long as the gradient of the metric is definable and defined. The MGRNN solves common practical problems of common feed-forward networks.